Synthesis and Spectral Studies of Mn(II), Co(II),Ni(II) ,Cu(II) Complexes with Mixed Ligands of Bipyridal and Tyrosine. - baqir, shymaa (Al-Qadisiyah Journal of Pure Science, 2017)
A new complexes of Mn(II), Co(II),Ni(II) and Cu(II) with mixed ligands of bipyridyl and tyrosine. All prepared compounds were identified by atomic absorption, (C.H.N) analysis, FT.IR and UV-Vis spectroscopic methods as well as magnetic susceptibility and conductivity measurements. From the above data the octahedral structure was suggested for all prepared complexes.